EU ENERGY UNION: ADJUSTMENT TO THE NEW DEVELOPMENT CYCLE - Spiridonovs, Jurijs; Bogdanova, Olga (Copernican Journal of Finance & Accounting, 2017)
Purpose – The purpose of this paper is to reflect the results of the research on the recent EU European energy policy following the launch of the concept of the Energy Union in February 2015. The authors analyse the issue of interdependency of the dimensions of the EU Energy Union: energy security, solidarity, trust, internal market, moderation of demand, decarbonisation, research, innovation and competitiveness. Design/methodology/approach – The paper summarizes the analysis performed by the various professionals and scientists in order to propose new methodology in evaluation the status of implementation of the energy policy. For the study the authors have used generally accepted quantitative and qualitative methods of economic science, inter alia comparative analysis, parameter estimation, grouping, economically mathematical modelling, synthesis, inductive, deductive, logically constructive and expert evaluation methods. Findings – The next step for successful realization of the EU Energy Union strategy is thorough planning for implementation of each of the defined instruments. Taking into account that fact that usually competences for practical transposition of different actions (mostly in form of legal acts) falls under responsibility of different institutions (both – regional and national), it is important to ensure an excellent coordination and constant cross-checking to avoid decrease of potential synergies between the benefits provided by the five dimensions. Originality/value – The concept of the EU Energy Union in terms of planning the energy policy is relatively new, however energy is one of the fundamental sectors of economy having significant impact on the development of any country. The authors propose original methodology in measuring the correlation of different dimension of energy policy.